(untitled) (London Journal of Medical and Health Research, 2024)
Introduction: In this work we will approach a clinical case of hereditary multiple exosthesis with malignant transformation. The pathogenesis of HMS is still unknown, and its clinical diagnosis, usually in the first decade of life, is associated with imaging exams. In cases of suspected malignancy, which is rare, the anatomopathological study is also used. Discussion: EHM, an autosomal dominant disease with complete penetration, is the most common skeletal development abnormality. It is usually easy to diagnose due to the age group of those affected, and clinical characteristics, such as short stature and osteoarticular deformities. In the case of atypical forms and rare hypotheses of malignancy, more sophisticated imaging and anatomopathological exams are needed to conclude the diagnosis. Treatment is expectant, or surgical when there is compromised quality of life and tumor malignancy. Conclusion: HMS is a common bone disease and rarely becomes malignant. However, it is extremely important to detect this abnormality, based on physical examination and imaging exams, to establish the correct early treatment, and thus prolong the survival and quality of life of patients affected by it.